Aplicabilidad del Modelo de Información de Edificios en el ámbito geoespacial para apoyar el Plan Maestro de Desarrollo Físico y Tecnológico de la Universidad Distrital - Perez Castillo, José Nelson; Rodríguez Molano, José Ignacio (Ingeniería, 2008)
Some tasks in the higher education in Colombia such as master plans are usually managed by using a Geographical Information System (GIS), as the tasks in these processes require a high level and amount of integrated geospatial information. Nowadays, Building Information Models (BIMs) have the capacity for encompassing building geometry, spatial relationships, geographic information, and properties of the components related to physic development plan. In this context, the Distrital University Francisco José de Caldas at Bogotá, Colombia integrates these domains according to institutional development plan. This research has demonstrated that it is possible to transfer information acquired from BIMs into the geospatial environment. The results also confirmed that BIMs provide a sufficient level and amount of information for the seamless integration between geographic information and building information.